Fucoxanthin Enhances Chain Elongation and Desaturation of Alpha‐Linolenic Acid in HepG2 Cells. Issue 10 (14th August 2015) - Wu, Meng‐Ting; Su, Hui‐Min; Cui, Yi; Windust, Anthony; Chou, Hong‐Nong; Huang, Ching‐jang
Abstract: Dietary fucoxanthin (FX), a carotenoid compound from brown algae, was found to increase docosahexaenoic acid (DHA, 22:6n‐3) and arachidonic acid (ARA, 20:4n‐6) in the liver of mice. DHA and ARA are known to be biosynthesized from the respective precursor α‐linolenic acid (ALA, 18:3n‐3) and linoleic acid (LNA, 18:2n‐6), through desaturation and chain elongation. We examined the effect of FX on the fatty acid metabolism in HepG2 cells (Hepatocellular carcinoma, human). In the first experiment, cells were co‐treated with ALA (100 μM) and FX (0–100 μM) or vehicle for 48 h. FX increased eicosapentaenoic acid (EPA, 20:5n‐3), docosapentaenoic acid (DPA, 22:5n‐3), DHA at concentrations of ≥50 μM. To clarify the change in the metabolism of polyunsaturated fatty acid (PUFA), in the second experiment, cells were co‐treated with universally‐[ 13 C]‐labeled (U‐[ 13 C]‐) ALA (100 μM) and FX (100 μM) for 0.5, 3, 6, 24 and 48 h. [ 13 C] labeled‐EPA, DPA and DHA content in HepG2 cells were all increased by FX after 48 h treatment. Furthermore, estimated delta‐5 desaturase (D5D) but not delta‐6 desaturase (D6D) activity index was increased at 48 h. These results suggested that FX may enhance the conversion of ALA to longer chain n‐3 PUFA through increasing D5D activity in the liver.